Sistem Ketenteraan Kerajaan Madinah Pada Zaman Nabi Muhammad S.A.W. - W. Ahmad, W. Yahaya (Jurnal Usuluddin, 1996)
This article describes the existance of the Islamic Government in Madinah headed by Rasulullah s.a.w. Under his administration, offices were introduced. One of them was the Arm Forces. This writing explains how the office was organised by the prophet, this included the appointment of the military chiefs.